Women, Piety, and Religious Behavior (Case Study of the Muslimah Ummahat Sholehah Community in Sukodono Tahunan Jepara) - Saefudin, Ahmad; Arif, Mahmud; Karwadi, Karwadi; Rahmawati, Affiyah; Paduka, Wanamean; Andriyani, Santi (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2023)
This study aims to describe the manifestation of piety constructed by women who are members of the Muslimah Ummahat Sholihah Community. Also, to analyze the level of their religious behavior. This research is a qualitative descriptive study that emphasizes field research. Researchers used observation techniques, interviews, questionnaires, and documentation to collect data. It turns out that the manifestation of women's piety is manifested by being obedient to the commands of Allah and His Messenger through the intermediary of teachers, covering their genitals and wearing the hijab, obeying their husbands, balancing ritual worship with social activities, and participating in religious activities. Meanwhile, the level of religious behavior of members of the Muslimah Ummahat Sholihah Community based on the results of the distribution of the questionnaire is categorized as high. Thus, the symbol of piety that they carry has absolutely nothing to do with conservatism, even radicalism, as some observers have alleged.